Access mechanism using inter planetary file system - Konala, Pandu Ranga Reddy; SaiAbhinav Reddy, V.; Krishna Chaitanya Varma, D.; G, Radhika (International Journal of Engineering and Technology, 2019)
Withthe advent of Internet of Things, trust is one of the important factor for provisioning secure, reliable, seamless communications and services. Connected devices are the order of the day, where IoT plays a vital role in the functioning. However, these IoT devices use various protocols for communication mostly a centralized architecture for data transfer. Some of these protocols are Message Queue Telemetry Transport (MQTT), which is a Pub-Sub (publisher and subscriber) protocol used for a device-to-device communication on TCP through a broker. This centralized server can be a third party service provider, which again raises the issue of trust. To address this, we propose a decentralized and distributed network architecture called Inter Planetary File System (IPFS) is used instead of third-party service provider. IPFS enables publish â€“ subscribe model similar to MQTT, but by removing the broker and making a peer-to-peer communication. Peer-to- peer architecture has its own challenges like security. The issue of security is also addressed by encrypting the files or data that has to be sent over the IPFS network using PGP (Pretty Good Privacy).Â Â Â